DELIBERATE SELF-POISONING IN ADOLESCENTS: A 3-YEAR SINGLE CENTRE STUDY - Šajinović, Slobodan; Stojadinović, Aleksandra; Bošković, Nikola; Andrić, Vanja; Tomić, Velimir; Savic, Aleksandra; Bukvić Šajinović, Aleksandra (Acta medicae Medianae, 2026)
Adolescence represents a period during which a child, in a transition period to adulthood, undergoes significant changes, often accompanied by risky behaviors such as intentional self-poisoning. This study aimed to identify the sociodemographic characteristics of adolescents, substance distribution and the impact of school success and completeness of the nuclear family on self-poisoning incidents. A retrospective study examined the records of 412 patients treated at the Institute for Child and Youth Health Care of Vojvodina over a three-year period. The average age of the patients was 15.7 ± 1.8 years. The most commonly used substances were alcohol (67%), benzodiazepines (23.6%), and cannabis (5.8%). One-fifth of the subjects took at least two substances simultaneously, with a higher frequency among female adolescents who experienced more frequent episodes of repeated self-poisoning. Half of the subjects (51%) lived in complete nuclear families, and a significant difference was found regarding alcohol consumption compared to other subjects. There is a significant difference in the consumption of benzodiazepines and alcohol concerning academic success. Alcohol and benzodiazepine medications were most commonly used for self-poisoning, with a significant gender difference. Due to the widespread availability of benzodiazepine medications, they were the most frequently used drugs. Girls were at a higher risk of repeated self-poisoning. Adolescents living in complete nuclear families with excellent academic success more often consumed alcohol, while those from incomplete families with poor success more frequently consumed benzodiazepines.